Conserving and contextualizing national cultural heritage: the 3-D digitization of the fort at al-Zubārah and petroglyphs at Jabal al-Jusāsiyyah, Qatar (poster) - Moulden, Helen; Cuttler, Richard; Kelleher, Shane (Proceedings of the Seminar for Arabian Studies, 2011)
While heritage monuments are all three-dimensional (3-D) objects within the landscape, the potential for recording and analysis of such objects in 3-D environments has only recently been realized. This presents the opportunity not only for point-in-time digital records that are accurate to the nearest millimetre, but has implications for the display of heritage both in museums, across the web, and for the placing of objects within their historical context. The fort at al-Zubārah and the petroglyphs at Jabal al-Jusāsiyyah are two of the most important yet antithetical heritage sites in Qatar, each of which was laser-scanned as part of an investigation into the potential for 3-D datasets to advance research, analysis, and conservation on two diverse sites.